Social Interaction of Students With Intellectual Disabilities at SMP Negeri 5 Sangatta Utara - Hastuti, Nanna Tri; Mumpuniarti, Mumpuniarti (Jurnal Syntax Transformation, 2025)
This study aims to describe the challenges faced by students with intellectual disabilities in developing social interactions, as well as the roles and strategies of teachers in supporting these interactions within inclusive education settings. The research was conducted at SMP Negeri 5 Sangatta Utara using a qualitative descriptive method, which emphasizes an in-depth understanding of phenomena through observation, interviews, and documentation. The research subjects consisted of a student with intellectual disabilities, peers, and classroom teachers. The findings reveal that students with intellectual disabilities experience difficulties in initiating and maintaining interactions, expressing opinions during group activities, and understanding social norms such as turn-taking and emotional expression. These limitations often lead to withdrawal and dependency on close peers. However, teacher interventions through participatory learning, peer mentoring, the use of visual and play-based learning media, and cooperative learning methods have proven effective in enhancing student engagement and communication. The study highlights the vital role of teachers as facilitators in fostering inclusive learning environments that promote empathy, social acceptance, and meaningful participation. Strengthening teacher competence and the availability of Special Assistant Teachers (GPK) are recommended to optimize the social and emotional development of students with intellectual disabilities in inclusive schools.